Hedonic Price Analysis for Consumer Preference on Rice Quality Attributes in Some Selected State of North Western Nigeria. - Abubakar, Bello Bunza; Abdullah, Abubakar Ngaski; Jabo, Muhammad Sani Muhammad (Pattimura University Ambon Maluku Indonesia, 2025)
Rice consumption in Nigeria has grown tremendously over a few decades, particularly among urban dwellers. The country also ranks first as both producer and consumer of rice in the West African sub region. Consumption is expected to continue to increase with population growth, urbanization and changes in consumption habits. This study investigated the influence of rice attributes on price. A total of 156 rice samples were collected from 15 markets within the radius of 400 km from the site of Middle Rima River Valley Irrigation Scheme in Nigeria, which were analysed for grain physical and chemical quality characteristics, which were subjected through a hedonic price analysis of different rice types sold in the markets. Results show that some markets had significant discount effect on price of rice while consumers pay premium price on imported rice. These findings suggest that the consumers preferred rice more appealing physical attributes such as low percent broken, high length to width ratio, low varietal mix and low impurities. This is despite the nutritional ascendance, demonstrated by high amylose and protein contents of domestic rice over the imported. The wide price differentials between domestic and imported rice could be bridge with improvement in the physical attributes of domestic varieties and better post-harvest handling techniques to reduce brokenness and impurities of the domestic rice. There is also need for advocacy of the nutritional in order to narrow the gap in consumer’s preference towards the domestic rice.